2021
DOI: 10.1038/s41598-021-94199-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors related to ambulation deterioration after 1-year of geriatric hip fracture in a Chinese population

Abstract: The objective of this study was to investigate the prognostic factors predicting the ambulation recovery of fragility hip fracture patients. 2286 fragility hip fracture patients were collected from the Fragility Fracture Registry in Hong Kong. Predictive factors of ambulation deterioration including age, gender, pre-operation American Society of Anesthesiologists grade, pre-fracture mobility, delay to surgery, length of stay, fracture type, type of surgery, discharge destination and complications were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…In accordance with the previous study, gender was an insignificant predictor of functional ability [27]. Our findings regarding the prevalence of hip fractures among females are also consistent with those of numerous other studies in many countries worldwide and indicate that females are more likely to experience hip fractures than males [34,35]. The evidence highlights that the biological and physiological differences between genders might influence both bone health and functional recovery.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the previous study, gender was an insignificant predictor of functional ability [27]. Our findings regarding the prevalence of hip fractures among females are also consistent with those of numerous other studies in many countries worldwide and indicate that females are more likely to experience hip fractures than males [34,35]. The evidence highlights that the biological and physiological differences between genders might influence both bone health and functional recovery.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that old age negatively affects ambulatory functional outcomes in patients with hip fractures. Wong et al [25] also argued that the risk of ambulation deterioration increased every 10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that old age negatively affects ambulatory functional outcomes in patients with hip fractures. Wong et al [25] also argued that risk of ambulation deterioration increased for every 10 years of age.…”
Section: Discussionmentioning
confidence: 99%